Humor in Conversation: Flouting Maxims in the 'Close the Door' Podcast - Zelianti, Syafina; Degaf, Agwin; Baswarudin, Fuad; Guktomo, Guktomo (Journal of Advanced Multidisciplinary Research, 2024)
This study analyzes an episode of the "Close the Door" podcast by Deddy Corbuzier, featuring comedian Komeng, with a focus on Grice's cooperative principle and Attardo's humor theory. The research aims to identify instances where conversational maxims—quantity, quality, relevance, and manner—are flouted to create humor. Using a descriptive qualitative approach, the study examines transcribed segments of the podcast episode. The findings reveal that the maxim of relevance was the most frequently flouted, appearing in 44.4% of cases, followed by the maxim of quantity at 33.3%. The maxims of quality and manner were each flouted in 11.1% of instances. These floutings often served to introduce humor through unexpected or exaggerated responses, engaging the audience and enhancing the podcast's entertainment value. This analysis contributes to the understanding of how conversational norms are strategically flouted in comedic contexts to generate humor. Further research is suggested to explore these aspects across different cultural and media settings, potentially incorporating quantitative methods to broaden the scope of analysis. This study provides insights into the linguistic strategies employed in digital media to engage audiences, highlighting the role of humor in communication.